2014
DOI: 10.1002/ajmg.a.36714
|View full text |Cite
|
Sign up to set email alerts
|

A novel variant in GABRB2 associated with intellectual disability and epilepsy

Abstract: The γ-aminobutyric acid type A (GABAA) receptor is one of the three main classes of receptors activated by GABA, the principal inhibitory neurotransmitter in the central nervous system. Mutations in genes encoding various subunits of this receptor (GABRA1, GABRA2, GABRA4, GABRA5, GABRA6, GABRB1, GABRB3, GABRG1, GABRG2, GABRG3, and GABRD) are implicated in a number of neurological and developmental disorders, including epilepsy and autism. To date, no human genetics studies have implicated mutations in GABRB2, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
55
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 64 publications
(60 citation statements)
references
References 31 publications
2
55
0
Order By: Relevance
“…This gene was found to be related to mental diseases, like schizophrenia [33, 34]. A recent study revealed that GABRB2 is highly upregulated in thyroid cancer [35].…”
Section: Discussionmentioning
confidence: 99%
“…This gene was found to be related to mental diseases, like schizophrenia [33, 34]. A recent study revealed that GABRB2 is highly upregulated in thyroid cancer [35].…”
Section: Discussionmentioning
confidence: 99%
“…One de novo GABRB2 variant, in the N-terminal extracellular domain implicated in GABA-binding, has been reported in a patient with ID and febrile seizures, tonic clonic convulsions, and partial seizures. 68 Variants in other genes encoding GABA type A-receptor subunits have been identified in different epilepsy syndromes, making GABRB2 a likely explanation for the phenotype in our patient.…”
Section: Resultsmentioning
confidence: 74%
“…Sequence variants of unknown significance in GABRB2 could possibly contribute to intellectual disability and epilepsy (Srivastava et al, 2014). An association with autism has been reported for SNPs in GABRA4 and an association with generalized epilepsy has been suggested for GABRA6 (Ma et al, Prasad et al, 2014).…”
Section: Known Consequences Of Genetic Variation In the Gabaergic Systemmentioning
confidence: 99%